EXPLORING COGNITIVE AND AFFECTIVE WISDOM IN C. S. LEWIS' CHRONICLES OF NARNIA: INSIGHTS INTO THOUGHT AND EMOTION - Belangi, Nadia Adinda; Purwarno, Purwarno; Hariati, Puji (JOURNAL OF LANGUAGE, 2024)
This qualitative study offers a comprehensive exploration of the complex wisdom embodied by Aslan, the central figure in C.S. Lewis's celebrated work, The Chronicles of Narnia. Grounded in Sternberg’s balance theory of wisdom, this research investigates both the cognitive and affective dimensions of Aslan's wisdom. Employing Creswell's thematic analysis approach, we closely examine Aslan's character to reveal a range of attributes that underpin his wisdom. Findings indicate that Aslan’s cognitive wisdom encompasses a profound understanding, strategic foresight, empathy, moral discernment, and a balanced response to adversity. These elements underscore his deep insight and the capacity to navigate complex moral landscapes. Moreover, his affective wisdom emerges through his compassion, bravery, and moral leadership, as he guides Narnia’s inhabitants. Through his actions, speech, and interactions, Aslan exemplifies an understanding of emotions, human connection, and the transformative impact of love and forgiveness. This study contributes to a deeper appreciation of wisdom as portrayed in literary narratives, illustrating how Aslan’s character models an integrated, multifaceted concept of wisdom.